Load Capacity Factor and Financial Globalization in Brazil: The Role of Renewable Energy and Urbanization - Xu, Dace; Salem, Sultan; Awosusi, Abraham Ayobamiji; Abdurakhmanova, Gulnora; Altuntaş, Mehmet; Oluwajana, Dokun; Kirikkaleli, Dervis; Ojekemi, Opeoluwaseun (Frontiers in Environmental Science, 2022)
To mitigate environmental challenges and fulfill the Sustainable Development Goals, a broader and holistic ecological assessment is required. As a result, this research utilizes the load capacity factor, which is a distinct proxy of environmental deterioration that offers a detailed environmental evaluation measurement by comparing biocapacity and ecological footprint simultaneously. Moreover, the load capacity factor provides the combined attributes of the demand and supply-side of environmental quality. Therefore, this research scrutinized the effect of financial globalization, urbanization, economic growth, renewable, and nonrenewable energy usage on load capacity factor for the period stretching between 1970 and 2017 in Brazil. The bounds testing procedure for cointegration in combination with the critical approximation p-values of Kripfganz and Schneider (2018) disclosed a cointegrating association between load capacity and its regressors. The outcome of the ARDL method uncovered that economic growth, non-renewable and renewable energy reduce the load capacity factor, whereas, urbanization has no impact on load capacity factor in Brazil. However, financial globalization has a positive effect on load capacity factor in Brazil. Finally, the study uses the spectral causality test to assess the causality interaction between the observed parameters. The policymaker should take advantage of the opportunity by developing policies that encourage the openness of the economy to foreign investors. Keywords: load capacity, financial globalization, urbanization, renewable energy